The Discourse Function of Intonation in Central Kurdish: A Phonological Account - Saadi Hamid, Twana; Najm Taha, Tola (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This paper looks into the Discourse Functions of Intonation in Central Kurdish ( CK henceforth). Although it is assumed that intonation is attested universally, its discourse function may differ cross-linguistically. Intonation can contribute to discourse directly and indirectly. The present study focuses on the former function which includes signalling turn-taking, topic-initiation and achieving coherence. Intonation can express some extra discourse functions such as showing interest, attention and agreement amongst the interlocutors. The Intonation tools used to add to the meaning of the utterances are usually by varying the pitch. Even though some studies examined intonation in Kurdish, to the best of the researchers’ knowledge, no study has exclusively examined the discourse functions of intonation in CK. Therefore, this paper embarks on investigating the discourse functions that intonation can convey in CK. It is found out that rising the pitch signals the start of a new topic, and lowering the pitch indicates the end of a topic. Another finding of the paper was that CK interlocutors lower the pitch, reduce loudness and lengthen the final element to signal end-of-turn whereas final high pitch is typically used in lists, and when the speaker is unwilling to give up the turn. The paper also discovers that CK speakers use intonation to achieve cohesion. Finally, the study acknowledges that the findings are only applicable in standard cases and they are not applied across the board. The unexpected interruption of conversation is a case where the rules that govern the discourse functions of intonation are violated.